Pengaruh Lingkungan Sosial terhadap Keterlibatan Anak dalam Tindak Pidana - Agus Digdo Nugroho; Eko Prasetyo; Hamzah Robbani (Decisio: Jurnal Ilmiah Hukum, 2024)
Law plays a crucial role in regulating social behavior and enforcing rules in society. Indonesia is a nation based on the rule of law and expects its citizens to comply with it for the sake of harmony and collective prosperity. However, there are specific concerns regarding the juvenile justice system in Indonesia which is yet to be optimized. Social environmental factors, such as family dynamics and economic conditions, can influence the involvement of children in criminal acts. This research aims to explore the impact of the social environment on juvenile delinquency and seek preventive solutions. The methodology employed is a qualitative approach, gathering data through literature study observations. The results indicate that the quality of communication within families, peer associations, school culture, and economic factors influence juvenile delinquency. To prevent such behavior, there is a need to enhance communication and support within families, as well as other interventions that improve a child's social environment.